2016
DOI: 10.1111/ajad.12350
|View full text |Cite
|
Sign up to set email alerts
|

Gambling problems and comorbidity with alcohol use disorders in Chinese‐, Korean‐, and White‐American college students

Abstract: Background and Objectives This study examined gambling behaviors and the relationship between gambling problems and alcohol use disorders (AUDs) among Chinese-, Korean-, and White-American college students. Methods Participants were 678 (179 Chinese, 194 Korean, and 305 White; 50% female) 21 to 26 year-old (M = 22.0 +/− 1.36) students attending one university in California. The South Oaks Gambling Screen was administered to assess gambling behavior and the Semi-Structured Assessment for the Genetics of Alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Using data from the 1991–1992 NLAES to examine Asian American subgroups, Price et al reported lifetime DSM‐IV alcohol dependence was 12.8% in Japanese ( n = 314), 10.1% in Filipino ( n = 185), 9.7% in Korean ( n = 123), 4.5% in Chinese ( n = 230), and 3.4% in Vietnamese ( n = 89) adults. The finding that Koreans were twice as likely to have lifetime dependence as Chinese is consistent with results in a college student sample that found 10% of Chinese ( n = 179), 20% of Korean ( n = 194), and 33% of White ( n = 305) college students had a lifetime DSM‐IV AUD . Using NSDUH data from 1999 to 2002, Sakai et al found that among US lifetime alcohol users, past‐year DSM‐IV dependence was approximately 4% in full (single race) Native Hawaiian and Pacific Islanders, 3% in Koreans, 2% in Indians, Japanese, and Vietnamese, and 1% in Chinese and Filipinos, with higher prevalence in those who indicated multiple races compared with single race for Filipinos and Native Hawaiians.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…Using data from the 1991–1992 NLAES to examine Asian American subgroups, Price et al reported lifetime DSM‐IV alcohol dependence was 12.8% in Japanese ( n = 314), 10.1% in Filipino ( n = 185), 9.7% in Korean ( n = 123), 4.5% in Chinese ( n = 230), and 3.4% in Vietnamese ( n = 89) adults. The finding that Koreans were twice as likely to have lifetime dependence as Chinese is consistent with results in a college student sample that found 10% of Chinese ( n = 179), 20% of Korean ( n = 194), and 33% of White ( n = 305) college students had a lifetime DSM‐IV AUD . Using NSDUH data from 1999 to 2002, Sakai et al found that among US lifetime alcohol users, past‐year DSM‐IV dependence was approximately 4% in full (single race) Native Hawaiian and Pacific Islanders, 3% in Koreans, 2% in Indians, Japanese, and Vietnamese, and 1% in Chinese and Filipinos, with higher prevalence in those who indicated multiple races compared with single race for Filipinos and Native Hawaiians.…”
Section: Resultssupporting
confidence: 67%
“…Similarly, Barry and colleagues found ORs that were not significantly different for Hispanics and Whites for past‐year pathological gambling with AUD (6.8 for Hispanics vs. 6.2 for Whites), DUD (1.7 vs. 2.9), nicotine dependence (7.1 vs. 7.1), and any substance use disorder (3.7 vs. 6.7), although Hispanics had a significantly stronger relationship between subsyndromal gambling and any substance use disorder as well as nicotine dependence than Whites. Luczak and Wall found lifetime probable pathological gambling was significantly related to DSM‐IV AUDs among Chinese men (OR = 13.3) and White men (OR = 9.4), but not among Korean men (OR = 2.5), but no associations were significantly different for women.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations